Yoghurt Nabati dari Berbagai Sumber Tanaman: Tinjauan Formulasi, Fermentasi, Nilai Gizi, dan Stabilitas Produk (Literatur Review) - Fatimah Rahmi; Jeallyza Muthia Azra; Ice Yolanda Puri (Journal of Innovation Research and Knowledge, 2026)
Plant-based yogurt has emerged as an alternative to dairy-based fermented products in response to growing concerns about lactose intolerance, milk allergies, plant-based diets, health, and food sustainability. Although it has potential as an alternative food product, plant-based yogurt differs from dairy yogurt due to variations in the protein, lipid, carbohydrate, fiber, mineral, and antinutritional compound composition of its raw materials. This article aims to critically review the development of plant-based yogurt from various plant sources, focusing on formulation, fermentation, nutritional quality, physicochemical characteristics, and storage stability. The review focuses on coconut-, legume-, oat-, and almond-based yogurt. The literature indicates that legumes, particularly soybeans and pulses, offer advantages in terms of protein content and bioactive compounds but may present challenges related to beany flavor, antinutritional factors, and inconsistent rheological properties. Oats have the potential to provide dietary fiber and β-glucan, while almonds provide lipids and proteins and generally exhibit favorable sensory characteristics. Coconut has the advantage of its lipid content, which contributes to a creamy mouthfeel; however, its relatively low protein content requires formulation optimization to achieve adequate gel network formation. Lactic acid bacteria fermentation plays an important role in acid production, protein modification, partial reduction of antinutritional factors, metabolite formation, and maintenance of microbial viability. However, fermentation effectiveness is strongly influenced by the type of plant matrix and bacterial strain used. Therefore, the development of plant-based yogurt should focus on combining different plant sources, optimizing starter cultures, fortifying nutritional components, and controlling stability during storage.